2021
DOI: 10.1038/s41598-021-89308-y
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of α-defensin impairs intestinal metabolite homeostasis via dysbiosis in mouse chronic social defeat stress model

Abstract: Psychological stress has been reported to relate to dysbiosis, imbalance of the intestinal microbiota composition, and contribute to the onset and exacerbation of depression, though, underlying mechanisms of psychological stress-related dysbiosis have been unknown. It has been previously established that α-defensins, which are effector peptides of innate enteric immunity produced by Paneth cells in the small intestine, play an important role in regulation of the intestinal microbiota. However, the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 55 publications
0
29
1
Order By: Relevance
“…Enterochromaffin cells release serotonin both luminally and basally, thus, the decreased levels of Turicibacter reported in the reviewed studies may be associated with decreased colonic serotonin levels that arise from stress-induced alterations in enterochromaffin cell function, which may also have negative implications for vagal nerve signalling [124]. Regarding Allobaculum, Suzuki et al [76] reported that CSDS reduced faecal α-defensin levels, and this was positively correlated with Allobaculum abundance, indicating that CSDS disturbed Allobaculum abundance via perturbations in intestinal function of Paneth cells and likely also decreased the mucus layer of the intestinal barrier due to the close association of Paneth cells and the regulation of this important component. CUMS-induced alterations in Allobaculum abundance have been reported in female C57BL6 mice, however these were inconsistent across studies likely due to differing durations in the CUMS protocol [43,93].…”
Section: Gut Microbial Compositionmentioning
confidence: 98%
See 2 more Smart Citations
“…Enterochromaffin cells release serotonin both luminally and basally, thus, the decreased levels of Turicibacter reported in the reviewed studies may be associated with decreased colonic serotonin levels that arise from stress-induced alterations in enterochromaffin cell function, which may also have negative implications for vagal nerve signalling [124]. Regarding Allobaculum, Suzuki et al [76] reported that CSDS reduced faecal α-defensin levels, and this was positively correlated with Allobaculum abundance, indicating that CSDS disturbed Allobaculum abundance via perturbations in intestinal function of Paneth cells and likely also decreased the mucus layer of the intestinal barrier due to the close association of Paneth cells and the regulation of this important component. CUMS-induced alterations in Allobaculum abundance have been reported in female C57BL6 mice, however these were inconsistent across studies likely due to differing durations in the CUMS protocol [43,93].…”
Section: Gut Microbial Compositionmentioning
confidence: 98%
“…Paneth cells have also been demonstrated to have a close association with MUC2 in that its presence around Paneth cells facilitates the secretion of antimicrobial peptides into the mucus layer [81]. Suzuki et al [76] showed that CSDS had deleterious effects on the number of Paneth cells and their secretory granules in the small intestine.…”
Section: Intestinal Barrier Integrity Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…This review has mainly focused on the mechanisms underlying the effect of microbes on depression, but it is also important to understand how microbes are affected by changes in the host's psychological and physiological state. A very recent study showed that exposure to chronic stress reduced the secretion of α-defensins, effector peptides of innate enteric immunity produced by Paneth cells in the small intestine, which resulted in gut dysbiosis and an impairment of intestinal metabolite homeostasis [159]. To extrapolate the mechanisms revealed in animal studies to therapeutic effects in humans, it would be necessary to gain a deeper understanding of the bidirectional communication between the gut microbiota and brain.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…It was also observed that ISCs cluster which failed to produce Paneth cells turned into ISC-absent enterocysts with a limited life-span, which contain only enterocytes[ 33 ]. In addition to Dll1-induced inhibition against secretory differentiation, Paneth cells generate endogenous growth factors including Wnt-3, EGF and TGF-α, facilitating niche environment reconstitution and budding organoid maturation[ 30 , 39 ]. Accordingly, Paneth cells are regarded as essential niche cells for the ISC niche.…”
Section: Niche Cues Within the Microenvironment Of Iscsmentioning
confidence: 99%